Assessment of periodontal health among the inpatients with schizophrenia - Djordjević, Vladan; Jovanović, Mila; Stefanović, Vesna; Nikolić Jakoba, Nataša; Djokić, Gorica; Stašević Karličić, Ivana; Todorović, Ljubomir (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Many studies on oral health of psychiatric inpatients reported schizophrenia as the most common psychiatric disorder among their sample population. The available evidence suggests the higher prevalence and severity of periodontal disease among the psychiatric inpatients. The aim of this study was to evaluate periodontal health among the inpatients with schizophrenia and to consider possible risk factors for their current periodontal diseases. Methods. This cross-sectional study comprised 190 inpatients with schizophrenia at the Clinic for Psychiatric Disorders “Dr Laza Lazarevic” in Belgrade, and 190 mentally healthy patients at the Clinic for Periodontology and Oral Medicine, Faculty of Dental Medicine, University in Belgrade. The Community Periodontal Index for Treatment Needs (CPITN) and sociodemographic characteristics were registered in both groups as well as the characteristics of the primary disease among the inpatients with schizophrenia. Results. The patients in the study group had significantly higher scores of the CPITN (2.24 ± 0.98) than the patients in the control group (1.21 ± 1.10). Most of the patients in the study group had supra- , or subgingival calculi (46.8%), in contrast to the control group patients, who had in most cases gingival bleeding (45.8%). The periodontal pockets where detected in 35.8% of schizophrenic inpatients. The linear regression analysis showed that the gender and age were statistically significant predictors of the CPITN value among the inpatients with schizophrenia. Conclusion. The results of this study generally indicate the need for continuous research of psychiatric patients’ oral health, in order to determine the modes of its improvement. Similar studies should elucidate significance of psychiatric patients’ periodontal health and sensitize psychiatrists and psychiatric nurses to the oral problems of their patients.
Keywords: age factors; hospitals, psychiatric; oral health; periodontal diseases; periodontal index; risk factors; schizophrenia; sex